Suicidal ideation and adverse experiences among adolescents with their separated/divorced parents in Hue city - Tran, Thi Tra My; Tran, Binh Thang; Nguyen, Minh Tam; Vo, Nu Hong Duc; Nguyen, Van Thong; Nguyen, Ngo Bao Khuyen; Pham, Thi Thu Ha; Ho, Uyen Phuong; Vo, Hoang Linh; Luong, Thi Thu Tham; Hoang, Tuan Anh; Dang, Cao Khoa; et al. (Tạp chí Y Dược Huế, 2023)
Background: Suicide continues to be a leading cause of death worldwide. Recently, more than 45,000 children in the age group of 10 to 19 years died by suicide, making it the second leading cause of death in the age group of 15 to 19, surpassed only by traffic accidents, tuberculosis, and fighting. Objective: To determine the prevalence of suicidal ideation among adolescents whose parents are separated/divorced; and to explore the factors associated with suicidal ideation and describe adverse experiences among adolescents. Methods: A cross-sectional descriptive study was conducted in 309 adolescents with separated/separated parents in Hue City. Data was collected through direct interviews using a structured questionnaire. Suicidal ideation was defined as the presence of thoughts or plans related to suicide within the last 12 months. Multivariate logistic regression was applied to identify factors associated with suicidal ideation in adolescents with separated/ separated parents. Results: The study found that 15.5% (95% CI:11.7 - 20.1) of adolescents with separated /separated parents reported experiencing suicidal thoughts, in which men accounted 8.4% (95% CI:5.6 – 11.2) and women accounted 7.1% (95% CI:4.5 - 10.6). Several factors were identified as increasing the risk of suicidal ideation, including alcohol use (OR = 3.24; 95% CI:1.42 - 7.42), hyperactivity/inattention (OR = 4.96; 95% CI:1.58 - 15.605), and a poor quality of family relationships (OR = 4.82; 95% CI:1.26 - 18.50). On the contrary, certain factors were found to reduce the risk, including being in the 14-15 age group of 14- 15 (OR = 0.26; 95% CI:0.10 - 0.69) and participating in physical activity (OR = 0.44; 95% CI:0.21 – 0.94). Conclusions: The research highlights a significant percentage of adolescents with separated / divided parents who experience suicidal ideation. Therefore, it is imperative for families, schools, and society to develop comprehensive strategies to monitor and address various risky behaviours among students simultaneously.